The musical comicaly of Chiquinha Gonzaga and its resonance with the singing clowns of Brazil - Tibúrcio, Caísa (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
The present study had as intent the discussion of the possible relations between the musical repertoire of Chiquinha Gonzaga and the musicality explored by musical clowns. It is known that, by the ending of the 19th century and beginning of the 20th century, Brazil lived within a context of evident multiplicities and emancipatory political processes – abolitionism and the Proclamation of the Republic, for example. Despite the hegemonic expectations of the Brazilian political scenario, the counter-scene of the marginal movements evidenced popular artists, clowns, and “sidewalk poets”. In this context, Chiquinha Gonzaga emerges as one of the most representative voices of the national art. As a means of methodology, the crossing of existing documental data in the biography of Chiquinha Gonzaga and in research books on themes such as clownery and Brazilian circus proceeded. It was concluded that Chiquinha Gonzaga’s contribution, as a woman of the maxixe musical genre, reflected as musical comicality, fixed and vastly divulged by the singing clowns in circuses, in circus-theaters and in the growing phonographic industry.